Peripapillary ring: histology and correlations - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2014)
To assess the histologic correlate of the peripapillary ring (PPR) as the optic disc boundary, to measure it histomorphometrically and to assess its associations with glaucoma and axial length.Using a light microscope, we measured the width of the PPR and optic nerve pia mater. We additionally had measured the axial length, length of parapapillary beta and gamma zones, and thickness of the sclera and choroid.The study included 83 human globes with a mean axial length of 26.1 ± 3.3 mm (range: 20.0-35.0 mm). In the non-highly myopic (axial length <26.5 mm) non-glaucomatous eyes, mean PPR width was 55 ± 14 ?m (range: 26-88 ?m) and mean thickness of the optic nerve pia mater was 52 ± 22 ?m (range: 20-84 ?m). PPR width and pia mater thickness were significantly associated with each other (p = 0.001; correlation coefficient r = 0.37). PPR width increased significantly with longer axial length (p = 0.001; r = 0.35) and with the length of the peripapillary scleral flange (p = 0.02; r = 0.34). Pia mater thickness increased significantly with longer axial length (p = 0.03; r = 0.24) and with presence of glaucoma (p = 0.03). In eyes without parapapillary gamma zone, PPR was covered or was at least touched by the end of Bruch's membrane and separated the peripapillary choroid from the prelaminar optic nerve head tissue. In eyes with parapapillary gamma zone, PPR was the continuation of the optic nerve pia mater and reached the undersurface of the peripapillary retinal nerve fibre layer. In these eyes, Bruch's membrane started in a distance of up to 5 mm from PPR, and the thin space of peripapillary choroid ended by an attachment of Bruch's membrane to the thinned sclera.Peripapillary ring width (mean: 55 ± 14 ?m) increases slightly with longer axial length and is independent of glaucoma. It is strongly correlated with the pia mater thickness and is the continuation of the pia mater to the ocular surface.
EVALuna2:21189